Household heterogeneity and the price puzzle in a new Keynesian model - Ida, Daisuke (Journal of Macroeconomics, 2024)
This paper provides a new insight into the price puzzle using a new Keynesian (NK) model with household heterogeneity. To do this, we adopt a tractable heterogeneous-agent NK (THANK) model that nests the two-agent NK (TANK) and representative-agent NK models. We first demonstrate that when the share of liquidity-constrained (LC) consumers is high, the degree of inflation stabilization in the Taylor rule crucially affects whether the price puzzle occurs in the TANK model. Second, we show that regardless of the share of LC consumers, the price puzzle disappears in the THANK model with a discounted dynamic IS (DIS) curve. In contrast, for a compounded DIS curve, a higher share of LC consumers generates the price puzzle. Finally, we find that even in the case of a compounded DIS curve, reinforced interest rate smoothing can prevent the price puzzle.
Keywords: Monetary policy shock; Price puzzle; Tractable heterogeneous NK model; Two-agent NK model; Economics; Household heterogeneity